Allergy as Predisposing Factors of Recurrent Aphthous Stomatitis - Ariyati Yosi; Nurdiana, Nurdiana; Lubis, Nenni Dwi Aprianti (Dentika: Dental Journal, 2025)
Allergy is an abnormality or alteration in the immune system’s response to foreign proteins. The clinical presentation of allergic reactions can vary widely, including recurrent aphthous stomatitis in the oral cavity. Therefore, this study aimed to investigate the prevalence of allergy as a potential etiology of recurrent aphthous stomatitis. For the assessment, a descriptive design was used, comprising 50 patients diagnosed with minor-type recurrent aphthous stomatitis who met the inclusion and exclusion criteria. Diagnosis of recurrent aphthous stomatitis was established through the patient’s history and clinical examination. Subsequently, blood samples were taken to analyze the levels of IgE and eosinophils. This was followed by a computer-based analysis conducted to assess the prevalence of allergy history along with the levels of IgE and eosinophils. The results showed that 14 patients (28%) had a history of allergies, while laboratory examinations identified 29 patients (58%) with elevated IgE levels, and 13 patients (26%) had high eosinophil levels. This suggested that allergy could play a role in the predisposition of recurrent aphthous stomatitis. Consequently, allergy assessments were recommended for patients with recurrent aphthous stomatitis, using either allergy history or laboratory tests.